Gamification as Predictors of the Integration in Teaching (Docentes 2.0 Journal, 2021)
Currently, higher education demands that teachers innovate didactic resources by integrating Information and Communication Technologies (ICT) in teaching to awaken students' interest. The general objective was to develop gamification as a didactic strategy in first semester students of the Bachelor of Law degree at the Polytechnic University of Nicaragua, to strengthen the learning of the subject computer applications. In the methodology, the interpretive paradigm was used with a qualitative approach, a descriptive type applying the inductive-deductive method in the Research-Action design with a sample of 60 students. The results showed that the creation of the gamification proposal included the innovation of emerging methodologies integrating ICT through educational games; The implementation of gamification gave the students of the computer applications subject a pleasant and meaningful learning experience, increasing their interest-motivation to learn autonomously. Finally, it concluded that gamification is of great importance in higher education because it allows the development of cognitive skills and strengthens the teaching-learning process, promoting meaningful learning environments that help enrich the inherent technological competencies.
Keywords: Gamification; Predictors of Integration; ICT; teaching